Seasonal Effects of Environmental Factors on the Performance Parameters of Three Types of Silicon Solar Modules at NRIAG, Helwan, Egypt - Zenhom, Heba; Ghitas, Ahmed; Abulwfa, Ahmed; Harhash, Maha; El-Nawawy, M S El-Nawawy; Abdelwahab, Mohamed M. (Iraqi Journal of Science, 2025)
The performance of PV modules, which is evaluated under standard test conditions, rarely meets actual outdoor conditions due to the fluctuations of PV output readings. The present work investigates the behavior of performance parameters of three PV technologies, namely mono-crystalline, poly-crystalline, and amorphous, under variation of environmental factors (ambient temperature Ta, relative humidity R.H., and solar irradiance G) in the four seasons on clear sky days during the year 2021. The performance parameters include open circuit voltage Voc, short circuit current density Jsc, ideal output power density PD, and ideal efficiency ηo. The study employed the first-designed I-V logger as a prototype for data collection at the Helwan site. The results revealed that all electrical performance parameters of the three solar modules have seasonally changed with environmental factors. In this sense, the performance parameters of three modules were strongly affected by the temperature coefficient of conversion efficiency in the afternoon period of the day. As a result, the highest values of depression in the ideal efficiency (ηo) due to the effect of ambient temperature (Ta) were -0.6%, -0.57%, and -0.3% for mc-Si, pc-Si, and a-Si, respectively during the afternoon period in the summer season. While the greatest percentage drops in ηo values of mc-Si, pc-Si, and a-Si were -0.87%, -0.78%, and -0.32%, respectively, per unit increase in relative humidity (R.H.) over the winter.  On the other hand, the performance of crystalline Si PV technologies is more affected by solar irradiance than a-Si technology in the winter season. The obtained results provide a comprehensive understanding of the operating behavior of each solar PV module type, which will be utilized to optimize the PV power system at the considered site in the future.